RELATED LEARNING MOTIVATION AND SOCIAL ECONOMIC STATUS OF PARENTS WITH EYES OF LEARNING BASIC ELECTRICAL ENGINEERING TRAINING CLASS X LIGHT VEHICLE ENGINEERING SMK N 1 SEDAYU BANTUL LESSONS YEAR 2013/2014 - Binu Wisaksono; Pairun Roniwijaya (Jurnal Taman Vokasi, 2014)
The purpose of the study was ( 1 ) to determine whether there is a relationship with the learning motivation learning outcomes Eye Basic Training Electrical Engineering class X Light Vehicle Engineering SMK N 1 Sedayu Bantul; ( 2 ) to determine whether there is a relationship between Socio-Economic Status of Parents with learning outcomes Eye Basic Training Electrical Engineering class X Light Vehicle Engineering SMK N 1 Sedayu Bantul; ( 3 ) to determine whether there is a relationship Motivation Learning and Socio-Economic Status of Parents with learning outcomes Eye Basic Training Electrical Engineering class X Light Vehicle Engineering SMK N 1 Sedayu Bantul. The research hypothesis ( 1 ) There is a positive relationship with learning outcomes Learning Motivation Training Eye Basic Electrical Engineering class X Light Vehicle Engineering SMK N 1 Sedayu Bantul; ( 2 ) There Socioeconomic status Parents with learning outcomes Eye Basic Training Electrical Engineering class X Light Vehicle Engineering SMK N 1 Sedayu Bantul; ( 3 ) There is a relationship Motivation Learning and Socio-Economic Status of Parents with learning outcomes Eye Basic Training Electrical Engineering class X Light Vehicle Engineering SMK N 1 Sedayu Bantul.This research was conducted at SMK N 1 Sedayu Bantul academic year 2013/2014 in the second semester of academic year 2013 / 2014 population in this study were all students of class X TKR totaling 120 students and this study using simple random sampling technique Haryking nomogram calculations so 96 obtained as samples. This research is correlational and ex post facto categorized. With the questionnaire data collection techniques and documentation of learning outcomes.The validity of the items obtained from the product moment correlation. About the reliability obtained with the formula stated alpha and reliable. Before the data were analyzed first tested the prerequisite analysis of the normality test, linearity, and multicollinearity test. Analysis using partial correlation analysis and multiple regression analysis.Based on the analysis of the results obtained the following results : ( 1 ) There is a positive and significant correlation Motivation Learning ( X1 ) with the learning outcomes Eye Basic Training Electrical Engineering ( Y ) ; ( 2 ) There is a positive and significant relationship of Parents Socioeconomic Status ( X2 ) with learning outcomes Eye Basic Training Electrical Engineering ( Y ) ; ( 3 ) There is a positive and significant correlation Motivation Learning ( X1 ) and Socio-Economic Status of Parents ( X2 ) together to learn Eye Basic Training Electrical Engineering ( Y ) .